Re-introducing garbage architecture in the present setting establishing design applications for reused building material systems - Olalo, Kristin Faye Ma (2015)
The aim of this study is to demonstrate the applicability and timeliness of packaging waste reuse in architecture. Material selection process is a complex and delicate task influenced and determined by the number of building material options as well as numerous prerequisites and decisions. Recent studies now argue that the use of reused building materials, created from post-consumer or post-industrial sources, offers the advantage of additional performance benefits and the reduction of carbon emissions, the need for additional landfill space, and transportation and refinement costs. This study produced a data repository showing relevant information about the reused packaging material assemblies and four sets of reused building material assembly prototypes using glass bottle bricks, paper tubes, PET bottles and tin cans. A survey was also undertaken in order to assess the availability, and current pattern of distribution and reuse of the aforementioned materials. The results of the latter identified the common and available variety of packaging materials in junkshops and other establishments and were then used to begin the process of dimensional coordination with that of the existing reused packaging material assemblies while the wall prototypes were subjected to Axial Loading, Compressive Strength Tests, Capillary Absorption Tests, Fire Resistance Tests, and Comparative Costing Analysis. The study concluded that the four packaging materials used may be applied for several purposes and structures and can still be supported by the current market. Other packaging waste materials can also be used for reused building material assemblies. In total, this study is a demonstration that material reuse can offer solutions for the garbage crisis as well as lower construction costs.